2011
DOI: 10.1258/ijsa.2011.010259
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of condom use errors and problems for heterosexual anal and vaginal intercourse

Abstract: Condom use errors and problems were compared for anal and vaginal intercourse among a convenience sample of heterosexual men aged 18-66 years (n = 757). Men completed an online questionnaire for the last male condom use event for penile-anal (10.4%) or penile-vaginal (89.6%) intercourse. The prevalence of condom use errors and problems was similar regardless of intercourse type with a few exceptions; those reporting anal intercourse were significantly more likely to report using water-based (P < 0.001) and oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
1
10
0
2
Order By: Relevance
“…34 Moreover, data has shown male partners are more likely to make an error in condom use during penile-anal intercourse in comparison to penile-vaginal intercourse. 35 The lack of perceived risk combined with such errors could expose females who engage in anal intercourse to an increased risk of STI and HIV acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…34 Moreover, data has shown male partners are more likely to make an error in condom use during penile-anal intercourse in comparison to penile-vaginal intercourse. 35 The lack of perceived risk combined with such errors could expose females who engage in anal intercourse to an increased risk of STI and HIV acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…63 Condom use is often lower in heterosexual anal sex than in vaginal sex. 66,67 Some studies show that women are coerced or forced to have anal sex by their partners and in the context of transactional sex. 68,69 In cases of sexual assault, reports of forced anal penetration range between 13% and 22.5%.…”
Section: The Role Of Heterosexual Anal Intercourse In Hiv Transmissionmentioning
confidence: 99%
“…Education on how to apply and remove condoms during both vaginal and anal sex may be needed. A study of heterosexual men ages 18 to 66 found that condom use problems were common, and the researchers noted the need for the development of prevention programs for heterosexual men that focused on condom use errors and problems for penile-anal as well as penile-vaginal intercourse (Topping et al, 2011).…”
Section: Discussionmentioning
confidence: 99%